Related Party Transactions and Earnings Management - Linvani Kuan; Greg Tower; Rusmin Rusmin; J-L.W. Mitchell Van der Zahn (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
This study examines the association between related party transactions and earnings man-agement, based on a sample of 50 Indonesian publicly listed companies for the periods ending 2004 and 2005. The hypothesis developed in this study draw on past literature and the tenets of agency theory which suggest that the existence of related party transactions represent potential conflict of interest which may results in earnings management and appropriation by controlling shareholder to minority shareholders. The empirical findings of the study suggest that there is no statistically significant evidence of the association between related party transactions and earnings manage-ment attributes. Additional sensitivity analysis conducted with alternative measures of earnings management and related party transactions confirm the initial regression results. The results of this study suggest that the mere presence of related party transactions in Indonesian companies does not necessarily indicate that management engage in greater earnings management. This study pro-vides a valuable starting point for similar research in other developing countries.Keywords: Earnings management; Related party transactions; Indonesia